Tindak Pidana Money Politics Ditinjau dari Hukum Pidana Islam - Hanafi, Hanafi; Sitepu, Rajin (Universitas Muhammadiyah Ponorogo, 2025)
Politics and Islam are two concepts that cannot be separated, as Islam provides guidance for all aspects of life, including political and state affairs. In Indonesia, the practice of